Staging science on TV: Richard Hammond's Invisible Worlds, Richard Hammond's Miracles of Nature and Wild Weather with Richard Hammond. Issue 2 (1st September 2018) - Morris, Nigel
This article comprises two distinct parts. The first surveys the problems and aspirations associated with television representations of science. This historical overview contextualizes the second part, which extrapolates from textual analysis of three closely related, high-profile, peak-time BBC series. It seeks to demonstrate that, despite massive efforts and a shift in attitudes within the academy towards dissemination of knowledge over the last third of a century, many associated with initiatives in Public Understanding (or Awareness) of Science and Public Engagement in Science and Technology, there has been little progress in how scientific matters are represented. Examination of extracts from each series are used to argue that televised science draws upon the twin histories and discourses of the illustrated lecture and Victorian stage illusionism, each of which presented spectacle and sensationalism. Attention to the programmes' construction and implicit informing ideologies reveals their divergence from the expository mode that they ostensibly claim to belong to. While many Public Understanding efforts appear to involve a long-standing hermetic debate between scientists and journalists predicated on outmoded communications theories, textual analysis demonstrates that relatively unsophisticated television studies approaches may yet offer worthwhile contributions.